IMPLEMENTATION OF THE TALKBACK APPLICATION IN IMPLEMENTING THE LEARNING OF CLASS XI BRANJANGAN STUDENTS AT SLB STATE BRANJANGAN JEMBER - agus hermawan (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
This study aims to describe the application of the Talkback screen reader application in the implementation of learning for blind students in class XI at the Branjangan Jember State SLB and to examine the obstacles and solutions for implementing the Talkback screen reader application in the implementation of learning for class XI blind students at Branjangan Jember State SLB. By using a qualitative descriptive approach. Data analysis uses 3 stages, namely data reduction, data presentation, and drawing conclusions. The subjects in this study were 3 blind students. The results of this study are that the application of the Talkback screen reader application in the implementation of classroom learning has been going on since 2018. In its implementation, schools, teachers, and especially blind students have had many positive impacts, such as helping in learning and learning activities. However, these are still experiencing obstacles originating from school institutions, teachers and the children themselves. Another obstacle is due to the inadequate availability of funds. Of these constraints there are solutions that have been implemented and some are still in the planning stage.